SECOBISBENZYLISOQUINOLINE ALKALOIDS - CHEMISTRY AND PHARMACOLOGY: A REVIEW - Syed Fazal Hussain (Baqai Journal of Health Sciences)
Major secobisbenzylisoquinoline alkaloids have been reported from the families Berberidaceae and Annonaceae and to a lesser extent from Menispermaceae, Hernandiaceae, Ranunculaceae, and Atherospermataceae. A critical study on the structures of these alkaloids indicates that secobisbenzylisoquinoline alkaloids could be the first step towards catabolism of bisbenzylisoquinolines but unfortunately, very little pharmacological work has been carried out on secobisbenzylisoquinoline alkaloids. The present review highlights the chemistry and pharmacology of these alkaloids and structures of common secobisbenzylisoquinoline alkaloids isolated from various sources have been reported